Integration of hunger and hormonal state gates infant-directed aggression - Mingran Cao; Rachida Ammari; Maxwell X. Chen; Patty Wai; Bradley B. Jamieson; Swang Liang; Basma F. A. Husain; Aashna Sahni; Nathalie Legrave; Irene Salgarella; James MacRae; Molly Strom; et al. (Nature, 2025)
Abstract Social behaviour is substantially shaped by internal physiological states. Although progress has been made in understanding how individual states such as hunger, stress or arousal modulate behaviour 1–9 , animals experience multiple states at any given time 10 . The neural mechanisms that integrate such orthogonal states—and how this integration affects behaviour—remain poorly understood. Here we report how hunger and oestrous state converge on neurons in the medial preoptic area (MPOA) to shape infant-directed behaviour. We find that hunger promotes pup-directed aggression in normally non-aggressive virgin female mice. This behavioural switch occurs through the inhibition of MPOA neurons, driven by the release of neuropeptide Y from Agouti-related peptide-expressing neurons in the arcuate nucleus (Arc AgRP neurons). The propensity for hunger-induced aggression is set by reproductive state, with MPOA neurons detecting changes in the progesterone to oestradiol ratio across the oestrous cycle. Hunger and oestrous state converge on hyperpolarization-activated cyclic nucleotide-gated (HCN) channels, which sets the baseline activity and excitability of MPOA neurons. Using microendoscopy imaging, we confirm these findings in vivo, revealing that MPOA neurons encode a state for pup-directed aggression. This work provides a mechanistic understanding of how multiple physiological states are integrated to flexibly control social behaviour.